2009
DOI: 10.4314/jmbr.v7i1-2.44535
|View full text |Cite
|
Sign up to set email alerts
|

A study of personality And psychological distress among delusional halitosis patients.

Abstract: (5) patients with age range of 18-30 years and a mean age of 24 years (SD = 4.47) were included in the study. These individuals manifested multiple symptoms associated with distress and they experienced personal discomfort and social embarrassment leading to emotional distress. The study highlights the importance of assessing personality characteristics and psychological dysfunction of patients presenting with delusional halitosis. A multidisciplinary approach in the treatment of delusional halitosis cannot, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…This finding is consistent with the findings of previous research. Akhigbe et al found that people with halitosis were more introverted on the EPQ scale (Akhigbe et al, 2008). This may be caused by the fact that people with halitosis were more fearful of close contact, more concerned about the actions of others around them, and more affected by their halitosis.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with the findings of previous research. Akhigbe et al found that people with halitosis were more introverted on the EPQ scale (Akhigbe et al, 2008). This may be caused by the fact that people with halitosis were more fearful of close contact, more concerned about the actions of others around them, and more affected by their halitosis.…”
Section: Discussionmentioning
confidence: 99%